Nanomedicine potentiates mild photothermal therapy for tumor ablation - Zijun Jiang; Tianyi Li; Hao Cheng; Feng Zhang; Xiaoyu Yang; Shihao Wang; Jianping Zhou; Yang Ding (Elsevier, 2021)
The booming photothermal therapy (PTT) has achieved great progress in non-invasive oncotherapy, and paves a novel way for clinical oncotherapy. Of note, mild temperature PTT (mPTT) of 42-45 °C could avoid treatment bottleneck of the traditional PTT, including nonspecific injury to normal tissues, vasculature and host antitumor immunity. However, cancer cells can resist mPTT via heat shock response and autophagy, thus leading to insufficient mPTT monotherapy to ablate tumor. To overcome the deficient antitumor efficacy caused by thermo-resistance of cancer cells and mono mPTT, synergistic therapies towards cancer cells have been conducted with mPTT. This review summarizes the recent advances in nanomedicine-potentiated mPTT for cancer treatment, including strategies for enhanced single-mode mPTT and mPTT plus synergistic therapies. Moreover, challenges and prospects for clinical translation of nanomedicine-potentiated mPTT are discussed.